Beowulf - Clark, George (Twayne Publishers, 1990)
Provides in-depth analysis of the life, works, career, and critical importance of Beowulf
Description based on print version record
Keywords: Epic poetry; English (Old); Monsters in literature; Dragons in literature; Heroes in literature